ACUTE INVASIVE RHINOSINUSITIS: CASE REPORT - Marques, Pedro (2006)
Invasive Fungal Sinusitis is a disease which incidence has been rising, because of the intimate affinity with different types of immunologically compromised patients. This pathologic entity has different forms of presentation according to each specific type of histopathology. These different presentations have distincttreatment and prognosis.Due to the complications of the disease, the diagnosis must be done as soon as possible to achieve a better therapeutic result.The authors present a review about Acute Fungal Sinusitis - Mucormycosis, about a patient aged 57 years old, with aplastic bane marrow and diabetes,diagnosed and treated in the Haematology and Otolararyngology Departments of Hospital de S.João - Porto